Hubungan Usia saat Melahirkan dengan Gangguan Kesehatan Mental Postpartum - Azizah Fristi Wulandari; Safrina Dewi Ratnaningrum; Rahma Dian Hanifarizani (Journal of Issues in Midwifery, 2025)
ABSTRACTThe postpartum period is a complex phase of adaptation that increases maternal vulnerability to mental health disorders, in which maternal age at childbirth is assumed to play an important role in determining biological, psychological, and social readiness during the postpartum period. This study aimed to analyze the association between maternal age at childbirth and the likelihood of postpartum mental health disorders based on screening results. This study employed an observational analytic design with a cross-sectional approach involving 61 postpartum mothers selected using purposive sampling. Maternal age was categorized into high-risk age (<20 years and >35 years) and healthy reproductive age. The likelihood of postpartum mental health disorders was assessed using the Edinburgh Postnatal Depression Scale (EPDS). Data were analyzed using univariate and bivariate analyses with the Chi-Square test, supported by the Fisher–Freeman–Halton Exact Test, with a significance level of 0.05. The results demonstrated a significant association between maternal age at childbirth and the likelihood of postpartum mental health disorders (p < 0.05), where mothers in the high-risk age group showed a higher proportion of potential postpartum mental health disorders compared to those in the healthy reproductive age group. In conclusion, maternal age at childbirth is associated with the likelihood of postpartum mental health disorders; therefore, early screening and mental health monitoring should be prioritized for high-risk age groups.Keywords: maternal age, postpartum, mental health, postpartum depression, EPDSABSTRAKMasa postpartum merupakan periode adaptasi yang kompleks dan meningkatkan kerentanan ibu terhadap gangguan kesehatan mental, di mana usia ibu saat melahirkan diduga berperan dalam menentukan kesiapan biologis, psikologis, dan sosial ibu dalam menghadapi masa nifas. Penelitian ini bertujuan untuk menganalisis hubungan usia ibu saat melahirkan dengan kemungkinan gangguan kesehatan mental postpartum berdasarkan hasil skrining. Penelitian ini merupakan studi analitik observasional dengan desain cross-sectional yang melibatkan 61 ibu postpartum yang dipilih menggunakan teknik purposive sampling. Usia ibu dikategorikan menjadi usia berisiko (<20 tahun dan >35 tahun) dan usia reproduksi sehat. Kemungkinan gangguan kesehatan mental postpartum diukur menggunakan Edinburgh Postnatal Depression Scale (EPDS). Analisis data dilakukan secara univariat dan bivariat menggunakan uji Chi-Square serta diperkuat dengan uji Fisher–Freeman–Halton Exact Test dengan tingkat signifikansi 0,05. Hasil penelitian menunjukkan terdapat hubungan yang signifikan antara usia ibu saat melahirkan dengan kemungkinan gangguan kesehatan mental postpartum (p < 0,05), di mana ibu pada kelompok usia berisiko memiliki proporsi kemungkinan gangguan kesehatan mental postpartum yang lebih tinggi dibandingkan ibu pada usia reproduksi sehat. Kesimpulannya, usia ibu saat melahirkan berhubungan dengan kemungkinan gangguan kesehatan mental postpartum, sehingga skrining dini dan pemantauan kesehatan mental perlu diprioritaskan pada kelompok usia berisiko.Kata kunci: usia ibu, postpartum, kesehatan mental, depresi postpartum, EPDS